Features of Low-Intensity Energy Balance in the Process of Physiotherapeutic Application of Mixtures of Natural Materials - О. П. Яненко; С. М. Перегудов; К. Л. Шевченко; О. Д. Головчанська (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2021)
The authors investigated the features of energy balance that provide the process of using natural materials in physiotherapeutic thermal procedures. Substances such as ozokerite, paraffin, naphthalene, muds and their combinations are widely used in physiotherapy, so it is important not only to know the parameters of the heat exchange, but also the distribution of other types of energy that can affect the effectiveness of treatment. The authors theoretically substantiated and experimentally proved that microwave component is presented in the radiation spectrum of the ozokerite applicator. The level of radiation in the millimeter range of the applicator with a size of 10x10 cm is compared with the level of low-intensity signals of technical devices for millimeter therapy. The dynamic change of the radiation level of the microwave component during the cooling of the applicator from the maximum temperature of 50°С to the temperature of the human body surface was investigated. It was revealed that the sign of the radiation of the millimeter component in relation to the human body changes. This results in the formation of positive and negative low-intensity flows of microwave radiation. The frequency ranges of these flows and their level were investigated. It has been found that changing the percentage of paraffin in ozokerite can affect the level and range of negative microwave flows. The results of previous studies by the authors, which substantiate the positive effect of negative flows, including ozokerite-paraffin therapy, in inflammatory processes with ''excess energy'' and other diseases, are adduced. The microwave electromagnetic radiation studied by the authors is a concomitant factor during the relevant physiotherapeutic procedures, in particular heat treatment. However, this factor can significantly affect the functional state of the human body, so it must be taken into account during physiotherapy procedures.